A novel clinical brain prognostic index for KRAS-mutated lung cancer and brain metastases (KRAS-BPI): Real-world evidence from two large European centers - Zerdes, Ioannis; Kamali, Caroline; Johannsdottir, Berglind; Blasi, Miriam; Assmann, Christin; Kazdal, Daniel; Stenzinger, Albrecht; Skribek, Marcus; Ekman, Simon; Christopoulos, Petros; Tsakonas, Georgios (Lung cancer, 2024)
Introduction - Several prognostic scores were developed for non-small-cell lung cancer (NSCLC) patients with brain metastases (BM), though limited data reported for the KRAS-mutated subgroup. KRAS-targeted therapies have improved extracranial and intracranial response, highlighting the need for reliable prognostic biomarkers. - Methods - A retrospective cohort (2010-2020) comprising 220 patients with BM KRAS-mutated NSCLC from two large academic Thoracic Oncology centers (Karolinska and Heidelberg) was analyzed. Clinicopathological parameters were collected from electronic health records. Prognostic factors of overall survival from BM diagnosis (BM-OS) were identified using Cox regression models. - Results - The median age at diagnosis was 65 years, with a female predominance (55.9 %). Adenocarcinoma was the dominant histological subtype, performance status (PS) was 0-2 in 91 % of the patients and one-third had > 4 BMs. Variables independently correlated with BM-OS included the presence of primary BM disease, PS, age, symptomatic CNS disease, extracranial metastases and number of BM, and were used to design a new KRAS-Brain Prognostic Index (KRAS-BPI). Patients with high-index score showed significantly longer BM-OS, compared to intermediate/low-index groups (median BM-OS = 30.0 vs 9.0 vs 2.0 months, respectively). - Conclusions - In the largest real-word data study of KRAS-mutated NSCLC patients with BM, we developed a novel prognostic tool for improved patient stratification.